Brain tumor-related epilepsy: an overview on neuropsychological, behavioral, and quality of life issues and assessment methodology - Maschio, Marta; Perversi, Fabio; Maialetti, Andrea (Frontiers in Neurology, 2024)
Brain tumor-related epilepsy (BTRE) is a rare disease in which brain tumor (BT) and epilepsy overlap simultaneously and can have a negative impact on a patient’s neuropsychological, behavioral, and quality of life (QoL) spheres. In this review we (a) addressed the main neuropsychological, behavioral, and QoL issues that may occur in BTRE patients, (b) described how BT, BTRE, and their respective treatments can impact these domains, and (c) identified tools and standardized evaluation methodologies specific for BTRE patients. Neuropsychological disorders and behavioral issues can be direct consequences of BTRE and all related treatments, such as surgery, anti-cancer and anti-seizure medication, corticosteroids, etc., which can alter the structure of specific brain areas and networks, and by emotional aspects reactive to BTRE diagnosis, including the possible loss of autonomy, poor prognosis, and fear of death. Unfortunately, it seems there is a lack of uniformity in assessment methodologies, such as the administration of different batteries of neuropsychological tests, different times, frames, and purposes. Further research is needed to establish causality and deepen our understanding of the interplay between all these variables and our intervention in terms of diagnosis, treatment, psychosocial assessment, and their timing. We propose that the care of these patients to rely on the concepts of “BTRE-induced disability” and “biopsychosocial model” of BTRE, to prompt healthcare providers to handle and monitor BTRE-related psychological and social aspects, as to maintain the patient’s best possible QoL.